2017
DOI: 10.5455/javar.2017.d193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high fructose administration on histopathology of kidney, heart and aorta of rats

Abstract: Objective: This study was conducted to assess the hazardous effects of high fructose administration on kidney, heart and aorta in rats. Materials and methods: Twenty adult healthy male albino rats weighing about 200-220 gm each were used in this study. The rats were divided into 2 duplicate groups; control group and fructose group. Fructose was administered to rats in fresh drinking water daily for 8 weeks (the whole experimental period). Serum urea, creatinine and sodium concentration were determined by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
5
9
0
1
Order By: Relevance
“…Unlike the chemically induced diabetes such as streptozotocin, where the metabolic derangements are due to the direct damage to the beta cells of the pancreatic islets 20 , here there were no marked changes observed in the heart and pancreas, except few mild hyaline degenerations in the myocardium and mild fibrosis in the exocrine part of the pancreas. Our findings were appeared similar to the previous reports on high fructose-induced metabolic syndrome in rats 21,22 . On the basis of the present investigation, overconsumption of high fructose for a prolonged period may imbalance the metabolism by accentuating obesity and inducing structural and functional changes in the liver and kidneys.…”
Section: Group I Group Ii Fig 1: Hande Stained Sections Of Kidneys Group I Normal Control Group Ii Fructose Group G-glomerulus (Yellow) Psupporting
confidence: 93%
“…Unlike the chemically induced diabetes such as streptozotocin, where the metabolic derangements are due to the direct damage to the beta cells of the pancreatic islets 20 , here there were no marked changes observed in the heart and pancreas, except few mild hyaline degenerations in the myocardium and mild fibrosis in the exocrine part of the pancreas. Our findings were appeared similar to the previous reports on high fructose-induced metabolic syndrome in rats 21,22 . On the basis of the present investigation, overconsumption of high fructose for a prolonged period may imbalance the metabolism by accentuating obesity and inducing structural and functional changes in the liver and kidneys.…”
Section: Group I Group Ii Fig 1: Hande Stained Sections Of Kidneys Group I Normal Control Group Ii Fructose Group G-glomerulus (Yellow) Psupporting
confidence: 93%
“…The absorbed photon energy in tissue with the same photon radiation frequency will be forwarded until the liver tissues by depolarization form meridian system. This information will be read as chemical information by nucleus and will stimulate the liver cells’ activity to generate the regeneration process, so it may accelerate the liver histopathology repair [34]. Meridian system, tissues that connected interior and exterior organs inside the body with body surface, is a point to achieve harmonic balance.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies reported similar histological and functional disruption following administration of HFD to animals [13,[15][16][17][18][19][20] . Consumption of HFrD also caused similar histological changes and dysfunction in rat kidney [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, these three genes were chosen as inflammation and glomerulosclerosis related genes in our study. Moreover, previous studies reported induction of necrosis in both glomeruli and tubular cells following consumption of HFD and HFrD [13,[15][16][17][18][19][20][21][22][23][24][25][26][27] . However, this conclusion based only on the histological examination, and none of these previous studies confirm the occurrence of necrosis at a molecular level.…”
Section: Introductionmentioning
confidence: 99%